2021
DOI: 10.1037/emo0000651
|View full text |Cite
|
Sign up to set email alerts
|

Altering emotions near the hand: Approach–avoidance swipe interactions modulate the perceived valence of emotional pictures.

Abstract: Approaching positive objects and avoiding negative ones are general action tendencies in human behavior. Interestingly, hand or arm positions connoting approach (arm flexion) or avoidance (arm extension) have also been shown to influence how the valence of a stimulus is evaluated. However, this causal effect on valence evaluation has been typically examined within experimental paradigms that do not require acting upon objects such as when touching or moving them. Accordingly, the current study attempts to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In contrast, avoidance behaviors serve to increase the distance to negative stimuli in order to minimize or prevent their unpleasant effects (cf. Cervera-Torres et al, 2019). Accordingly, it has been suggested that approach-avoidance behaviors may ground affective associations in terms of "close"-positive and "far"-negative (e.g., Van Boven et al, 2010; Davis et al, 2011).…”
Section: Valence Associations Across the Lateral Space: The Affectivementioning
confidence: 99%
“…In contrast, avoidance behaviors serve to increase the distance to negative stimuli in order to minimize or prevent their unpleasant effects (cf. Cervera-Torres et al, 2019). Accordingly, it has been suggested that approach-avoidance behaviors may ground affective associations in terms of "close"-positive and "far"-negative (e.g., Van Boven et al, 2010; Davis et al, 2011).…”
Section: Valence Associations Across the Lateral Space: The Affectivementioning
confidence: 99%
“…This allows us to answer the question whether the eAAMT is helpful at all. As second comparator, we chose to use the swipe-based AAMT which is currently the most common AAMT variant on the smartphone [ 39 41 , 52 , 53 ]. The comparison with a swipe-based AAMT allows us to investigate whether the use of emotions in the AAMT provides additional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Variants of this method include using mouse movements (e.g., [ 37 ]) or moving a manikin towards or away from a stimulus through key presses (e.g., [ 38 ]). Recent technological developments allow an adaptation of the paradigm for use on the smartphone, where participants are asked to swipe the stimuli on a touchscreen instead of using a joystick [ 39 ], greatly facilitating the dissemination of the intervention compared to desktop-based AAMTs (e.g., [ 40 , 41 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Affective valence, that is, how positive or negative we feel, in uences the way we interact with objects or people. Everyday objects elicit some form of valence [107], and we change our behaviors depending on how we perceive the valence [108]. We are generally skilled at evaluating affective valence when looking at realistic or cartoonish emotional expressions [102,[109][110][111], although exceptions occur when we confuse certain expressions (i.e., Surprise/fear) [112,113].…”
Section: Discussionmentioning
confidence: 99%